From Italy to Peru. The litographic work of Carlo Fabbri - Pachas Maceda, Sofía (2018)
This article deals with the lithographic work of Carlo Fabbri, one of the most talented Italian artists who came to Peru during the XIXth century. His remarkable works were published in magazines such as the well-known weekly El Perú Ilustrado (Illustrated Peru), in which he captures attention with original compositions that seem to be illustrated reports and pleasant scenes that need no words to provoke laughter.